AA Fragrana / Ainin Sofiya Hisham and Nur Adila Md Azman - Hisham, Ainin Sofiya; Md Azman, Nur Adila (2022)
AA Fragrana is a partnership business of a local brand that creates the value of perfume in the market. Our goal of selling this product is to be the biggest locally manufactured perfume brand that is recognized by the local community and also the overseas community like how SimplySiti and many more brands are recognized. We want to help to boost our customers’ confidence and be a mood booster when they are using our perfume because they feel nice and fresh. Our products are supplied by Flonerch. The perfumes are locally manufactured by using imported raw materials from France. AA Fragrana was established in June 2022. We are selling a type of Eau De Parfum which is called Love Letter. The product received good feedback from our beloved customers as they said it smells so good. Love Letter is an Eau De Parfum which can last up to 10 hours depending on where you spray it. Our products are special because the smell will change over time. For instance, for the first 15 minutes, you can smell pear, apple and plumscents and the next 30 minutes, you can smell cherry blossom, rose petals and lily scents. Musk, vanilla, sandalwood and amber can be smelled longer as it is a base note and it will last up to 10 hours. age because social media marketing is easier and cheaper for a small business like us. As customers are concerned about the alcohol contained in many perfumes from various brands, they do not need to worry about it with Love Letter because we use synthetic alcohol made from chemicals and it can be used for prayers and wudhu purposes. We sold 3 bottles of Love Letter in our second month operating the business and managed to get a total of sales of RM141. We promote and advertise our business through a Facebook